Laceration Extension in Median and Mediolateral Episiotomy - Bobby I Utama; Junizaf Junizaf; Budi I Santoso; Ermawati Ermawati; Surahman Hakim (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To compare the laceration extension between median and mediolateral episiotomy in women with perineal body sized more than 2.5 cm. Method: A singleâ€blind RCT study was conducted on 104 women receiving median episiotomy and 104 women receiving mediolateral episiotomy at Dr. M. Djamil Hospital Padang and Reksodiwiryo Military Hospital Padang. Result: There was no difference in laceration extension in both groups, but pain in the first 24 hours and pain after day 14 was higher on mediolateral group than the median group (p=0.005 and p=0.008, respectively). Conclusion: There is no difference in terms of laceration extension between median and mediolateral episiotomy, but the pain is higher in the mediolateral group. [Indones J Obstet Gynecol 2015; 1: 38â€43] Keywords: laceration extension, median episiotomy, mediolateral episiotomy